Breakdown of a defensive symbiosis, but not endogenous defences, at elevated temperatures. Issue 8 (23rd November 2017) - Doremus, Matthew R.; Smith, Andrew H.; Kim, Kyungsun L.; Holder, Angela J.; Russell, Jacob A.; Oliver, Kerry M.
Abstract: Environmental factors, including temperature, can have large effects on species interactions, including mutualisms and antagonisms. Most insect species are infected with heritable bacterial symbionts with many protecting their hosts from natural enemies. However, many symbionts or their products are thermally sensitive; hence, their effectiveness may vary across a range of temperatures. In the pea aphid, Acyrthosiphon pisum, the bacterial symbiont Hamiltonella defensa and its associated APSE bacteriophages confer resistance to this aphid's dominant parasitoid, Aphidius ervi . Here, we investigate the effects of temperature on both endogenous and symbiont‐based protection against this parasitoid. We also explored the defensive properties of the X‐type symbiont, a bacterium hypothesized to shape aphid defence when co‐occurring with H. defensa . We show that H. defensa protection fails at higher temperatures, although some aphid genotype and H. defensa strain combinations are more robust than others at moderately warmer temperatures. We also found that a single X‐type strain neither defended against parasitism by A. ervi nor rescued lost H. defensa protection at higher temperatures. In contrast, endogenous aphid resistance was effective across temperatures, revealing that these distinct defensive modes are not equally robust to changing environments. Through a survey of field‐collected pea aphids, we found a negative correlation between H. defensa frequencies and average daily temperatures across North American locales, fitting expectations for reduced symbiont benefits under warm climates. Based on these findings, we propose that rising global temperatures could promote the widespread breakdown of defensive mutualisms, a prospect with implications for both human and ecosystem health.